2023
DOI: 10.1002/chem.202300506
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Oxides‐Based Anode Materials for Alkali Metal‐Ion Storage

Abstract: With the increasing demand for renewable energy, alkali metal-ion (lithium/sodium/potassium-ion) batteries play more and more important roles in the field of static storage and electrical vehicle industry. Novel anode materials with high reversible capacity, safety and long-term cycling stability are desiderated to meet the ever-growing demand for alkali metal-ion batteries with high electrochemical performance. Antimony oxides (Sb x O y ) show electrochemical reaction activity with all of lithium, sodium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…528–537 Metal oxides, metal sulfides, metal selenides, and metal phosphides are the most representative conversion-type anode materials. 351,355,389,400,538–543 It should be noted that some of the energy storage contributions of sulfides ( e.g. , MoS 2 and ReS 2 ) and selenides ( e.g.…”
Section: Anode Materialsmentioning
confidence: 99%
“…528–537 Metal oxides, metal sulfides, metal selenides, and metal phosphides are the most representative conversion-type anode materials. 351,355,389,400,538–543 It should be noted that some of the energy storage contributions of sulfides ( e.g. , MoS 2 and ReS 2 ) and selenides ( e.g.…”
Section: Anode Materialsmentioning
confidence: 99%
“…[13,19] Researchers have found that the performance of electrode materials is a key factor affecting the improvement of battery performance in a large number of explorations. [20] Most of the traditional electrode materials are inorganic compounds, pure carbon materials and derivatives, such as metal phosphates, metal oxides [21][22][23] and graphite et al The larger radius of Na + , K + makes the resistance in the process of insertion/extraction in the host material significantly larger than that of Li + , which is the main reason for the generally lower specific capacity of the reported electrode materials for SIBs/PIBs. And in the cycling process, the volume change of the electrode materials for SIBs/PIBs is larger compared with that of LIBs, and the internal structure of the electrodes is more likely to be damaged, resulting in low cycling performance of battery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among these, antimony oxides (Sb x O y ) hold great competitive edges as alternative electrode materials for lithium-/sodium-ion batteries (LIBs/SIBs) on account of their high theoretical specific capacities (>1000 mA h g −1 ) according to the reversible conversion–alloying mechanism. 3–8 However, Sb x O y -based electrodes still suffer from inherent poor conductivity and structure collapse during repeated lithium/sodium-storage processes, causing unsatisfactory rate capability and severe capacity fading during cycling, which has delayed their practical application.…”
Section: Introductionmentioning
confidence: 99%